Navigating the Transition from Theory to Practice: A Phenomenological Inquiry into the Lived Experiences, Professional Identity Formation, and Well-Being of Pre-Service Teachers during School Deployment in Philippine Basic Education Settings - Rosemelita Valdez-Bastian, (The Bioscan, 2026)
This qualitative phenomenological study explored the lived experiences, professional identity formation, and well-being of pre-service teachers during their deployment in selected DepEd elementary schools in Echague, Isabela, namely Echague East Central School, Echague West Central School, Echague South Central School, and Soyung Elementary School. Using in-depth interviews, reflective journals, and field notes, the study examined how pre-service teachers made meaning of their transition from university-based learning to actual classroom practice. Findings revealed five major themes: confronting classroom realities, translating theory into adaptive practice, constructing professional identity through mentorship, sustaining emotional well-being amid practicum demands, and developing commitment to the teaching profession. The study showed that deployment served not only as a requirement for professional training but also as a transformative experience that shaped confidence, resilience, reflective thinking, and teacher identity. Results affirm that practicum experiences help pre-service teachers connect theory with practice, while mentorship, feedback, belongingness, and emotional support play crucial roles in their professional growth. The study recommends strengthened school-university partnerships, structured mentoring, reflective conferences, and well-being support mechanisms for pre-service teachers.